Music Therapy for Early Postoperative Pain, Anxiety, and Sleep in Patients after Mitral Valve Replacement - Zhang, Qi-Liang; Xu, Ning; Huang, Shu-Ting; Lin, Ze-Wei; Chen, Liang-Wan; Cao, Hua; Chen, Qiang (The Thoracic and Cardiovascular Surgeon, 2020)
Background To investigate the effect of music therapy on early postoperative pain, anxiety, and sleep quality in patients after mechanical mitral valve replacement (MVR).Methods A total of 222 patients undergoing mechanical MVR were divided into two groups: the music group and the control group. The patients in the music group received 30 minutes of music therapy every day, whereas the patients in the control group had 30 minutes of quiet time. The visual analogue scale (VAS) was used to evaluate the degree of pain, and the Self-Rating Anxiety Scale (SAS) was used to evaluate the degree of early postoperative anxiety. We also recorded the sleep duration of the patients and used the Verran and Snyder-Halpern (VSH) Sleep Scale to evaluate the sleep quality of the patients.Results The VAS scores in the music group were significantly lower than those in the control group, and early postoperative anxiety in the music group was also significantly improved compared with that in the control group. The sleep duration in the music group was significantly greater than that in the control group. In the evaluation of sleep quality using the VSH Sleep Scale, the scores for sleep interruption, sleep length, sleep depth, degree of rest, and subjective sleep quality in the music group were significantly lower than those in the control group.Conclusions Music therapy can be an effective intervention to reduce early postoperative pain, relieve early postoperative anxiety, prolong sleep time, and improve the sleep quality of patients after mechanical MVR.
Keywords: mitral valve surgery; music therapy; postoperative care